Efficacy and interaction of dicamba-haloxyfop tank mixtures (Revista de Ciências Agroveterinárias, 2021)
The application of herbicide tank mixtures is a common practice in agricultural settings, especially for controlling weed communities with mono and eudicotyledons species occurring simultaneously. Therefore, thisstudy was carried out with the objective of evaluating the effectiveness and interaction of dicamba-haloxyfop tank mixtures used to control four weed species. For this, four different experiments were conducted, each with one of the plant species, namely: sourgrass (Digitaria insularis), horseweed (Conyza spp.), morning glory (Ipomoea triloba) and goosegrass (Eleusine indica). In each experiment, the experimental design consisted of completely randomized blocks, in a 4x4 factorial scheme of treatments, totaling 16 treatments with five replications, i.e., 80 plots of each species. Four doses of the herbicide dicamba (480, 240, 120 and 0 g ha-1) and four doses of the herbicide haloxyfop (60, 30, 15 and 0 g ha-1) were adopted. Percentage control was evaluated at 14 and 28 days after application (DAA) and mass of dry matter was evaluated at 28 DAA. Antagonistic, additive and synergistic effects were observed for dicamba-haloxyfop tank mixtures, with a greater preponderance of additive effects. Considering all four plant species, in different doses and dates of evaluation, 72 dicamba-haloxyfop interactions were evaluated, in which 50 were considered additives. However, the possibility of antagonism (9 interactions) or even synergy (13 interactions) cannot be ruled out, subjected to the influence of the herbicide dose, plant species and moment of evaluation.
Keywords: ACCase inhibitors; auxinic herbicides; synergy; antagonism; additivity